Seasonal and geographical differences in the ruminal microbial and chloroplast composition of sika deer (Cervus nippon) in Japan - Shinpei Kawarai (Scientific Reports, 2022)
Abstract To understand the nutritional status of culled wild sika deer (Cervus nippon), we compared the ruminal microbes of deer living in habitats differing in food composition (Nagano winter, Nagano spring, and Hokkaido winter) using next-generation sequencing. Twenty-nine sika deer were sampled. Alpha and beta diversity metrics determined via 16S and 18S rRNA amplicon-seq analysis showed compositional differences. Prevotella, Entodinium, and Piromyces were the dominant genera of bacteria, fungi and protozoa, respectively. Moreover, 66 bacterial taxa, 44 eukaryotic taxa, and 46 chloroplastic taxa were shown to differ significantly among the groups by the linear discriminant analysis effect size (LEfSe) technique. Total RNA-seq analysis yielded 397 significantly differentially expressed transcripts (q < 0.05), of which 48 (q < 0.01) were correlated with the bacterial amplicon-seq results (Pearson correlation coefficient > 0.7). The ruminal microbial composition corresponded with the presence of different plants because the amplicon-seq results indicated that chloroplast from broadleaf trees and Stramenopiles-Alveolates-Rhizaria (SAR) were enriched in Nagano, whereas chloroplast from graminoids, Firmicutes and the dominant phylum of fungi were enriched in Hokkaido. These results could be related to the severe snow conditions in Hokkaido in winter and the richness of plants with leaves and acorns in Nagano in winter and spring. The findings are useful for understanding the nutritional status of wild sika deer.